Google Cloud Digital Leader Cert Prep: 2 Exploring Data Transformation with Google Cloud. - Cloud, Google (linkedin.com, 2024)
Explore topics related to data transformation with Google Cloud, and prepare for the Google Cloud Digital Leader exam.